Libraries, telecentres, cybercafes and public access to ICT : international comparisons - Gomez, Ricardo, 1964- (Information Science Reference, 2012)
"This book presents groundbreaking research on the new challenges and opportunities faced by public libraries, community telecentres, and cybercafes that offer public access to computers and other information and communication technologies"--Provided by publisher.